Predicting, monitoring, and assessing forest fire dangers and risks - Baranovskiy, Nikolay Viktorovich, 1978- (Engineering Science Reference, IGI Global, 2020)
"This book examines current research on predicting, monitoring, and assessing forest fire dangers and risks"-- Provided by publisher.
Keywords: Forest fires -- Prevention and control.; elektronické knihy; electronic books